Criminal Justice Student Views of the Criminal Justice System: The Impact of Education and Self-Selection and Their Implications for the Human Services - McCarthy, Belinda Rodgers (1981)
The present study examines criminal justice student views of the criminal justice system. The purpose of the research is to investigate issues surrounding the influence of self-selection and criminal justice education on the opinions of criminal justice students toward the criminal justice system. The research suggests that students choose criminal justice careers in part because their personal philosophies mirror the conflicting objectives of the criminal justice system. Criminal justice education seems to influence criminal justice student views of the criminal justice system, but in a direction that may make the transition to employment in criminal justice agencies a more difficult process. It is recommended that criminal justice and social work education include efforts to equip students with the understanding and skills needed to utilize what they have learned in human service agencies. Such preparation should include internship opportunities and coursework in organizational behavior and organizational change strategies